Youth perspectives on weight‐related words used by healthcare professionals: A qualitative study. (13th February 2020) - Stuij, Mirjam; van Maarschalkerweerd, Pomme E.A.; Seidell, Jaap C.; Halberstadt, Jutka; Dedding, Christine
Abstract: Background: Although healthcare professionals often consider body weight a sensitive and difficult topic to discuss with children, a contextualized and comprehensive understanding of youth perspectives on weight‐related words used in healthcare has yet to be established. This qualitative study aims to explore perspectives of Dutch children on the terminology healthcare professionals use when discussing weight. Methods: Fourteen interviews and one focus group discussion were held with children (age 8–16) who were in care because of their weight. A toolkit with customizable interview techniques was used in order to facilitate reflection and tailor the interview to each respondent. A narrative content analysis was conducted. Results: Respondents attached both clear and subtle differences in meanings to (certain) weight‐related words. Their perspectives were not unanimous for any single word. Moreover, at times, respondents framed certain words in positive or negative ways or used a word they disliked to describe themselves. This illustrates that meanings of weight‐related words are not fixed but context and situation specific. Conclusion: This study revealed that meanings children assign to weight‐related words are shaped by their experiences in the broader social context, especially at school, as well as with (previous) healthcare professionals. It pointed towards the importance of bedside manner, acquaintanceship, and support. Healthcare professionals treating children because of their body weight are advised to invest in a good patient–caregiver relationship, pay attention to children's previous (negative) social weight‐related experiences, and reflect critically on their own preconceptions about body weight and the impact these preconceptions might have on their patient–caregiver relationships.